A Computed Tomographic and Pathological Study of Equine Cheek Teeth Infundibulae Extracted From Asymptomatic Horses. Part 2: MicroCT, Gross, and Histological Findings - Horbal, Apryle; Smith, Sionagh; Dixon, Padraic M. (Frontiers in Veterinary Science, 2019)
Background: Equine maxillary cheek teeth infundibulae are frequently affected by developmental and acquired disorders, but the imaging, gross and histological features of normal and abnormal infundibulae remain incompletely understood. Objective: To perform MicroCT, gross examination and histology on sectioned teeth and compare the imaging and anatomical findings. Study design: Ex vivo original study. Methods: Eight maxillary cheek teeth of different ages and with varying grades of occlusal infundibular caries were extracted from equine heads obtained from an abattoir. The teeth were imaged by MicroCT, then transversely sectioned and grossly and histologically examined, with the imaging and anatomical findings compared. Results: Histologically, hypoplastic cemental areas consisted of irregularly-shaped, wide central channels, with multiple, cylindrical side-branches that extended peripherally to a variable extent. Cementum with extensive, wide, empty channels and cementum with a more irregular moth-eaten appearance had low HU on CT. Some infundibulae had cement-free areas that only contained fragments of collagen-like material, especially at their apical aspects. Carious subocclusal areas had connections with the occlusal surface and had disrupted cemental architecture, including of their central vascular channel that, along with their side branches, contained degraded food and cemental debris. Main Limitations: No clinical histories or accurate ages were available for these teeth. Conclusions: Hypoplastic cemental lesions, including at central linear and apical sites, histologically contain areas with multiple wide-branched cylindrical channels or even areas of total cement hypoplasia and when such cemental defects contact the occlusal surface, food impaction and caries can ensue. There was no clear cut distinction between “normal” infundibular vascular channels and central linear hypoplastic defects.